Representasi Pernikahan Dini Pada Sinema Indonesia - Ikasari, Prinisia Nurul; Christiani, Lintang Citra (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2023)
Abstract. The socio-economic impact of the COVID-19 pandemic on households in Indonesia has also had an impact on increasing child marriage at an early age. This is also supported through the understanding of women and men in marriage which is manifested through media messages. Likewise when talking about early marriage. This research wants to see how the representation of early marriage through cinema in Indonesia. Theory of Representation, Women's Inferiority, The Concept of Film in Mass Media, is used as a support for the analysis. The research was conducted using a qualitative descriptive approach using the critical discourse analysis model of Norman Fairclough. Norman Fairclough's critical discourse is considered appropriate to see the representation of women through cinema in Indonesia with the theme of early marriage because this approach looks at not only the text dimension, but also sociocultural practices and discourse practices. The results of this study indicate that the representation of women through cinema in Indonesia with the theme of early marriage is related to several discourses namely, religious discourse, sexuality and virginity discourse, marriage discourse and discourse on love. The text in Yuni's film keeps the discourse on love in marriage away or at least shifts the meaning of love. The meanings that appear in texts about women, marriage, and love in film texts are determined by the prevailing culture in society and in turn have an impact on women's decision-making if they are internalized and considered as truths that need not be questioned.